Magnetic focusing and trapping of high-intensity laser-generated fast electrons at the rear of solid targets. - Davies, JR; Bell, A; Tatarakis, M (1999)
The transport of fast electrons generated by a 1 ps, 20 J, 10(19) W cm(-2), 1 microm wavelength laser pulse through 70-250 microm thick deuterated polyethylene (CD2) targets is modeled with a Fokker-Planck hybrid code in r-z geometry. Initially, electric field generation inhibits propagation, which then proceeds by the formation of a low resistivity channel due to Ohmic heating. The magnetic field generated at the edge of the channel leads to strong collimation. This is observed for a wide range of parameters. Reflection of electrons at the rear surface forms a magnetic field which focuses the incident electrons on to the rear surface and forces the reflected electrons outwards. This would lead to the formation of a small diameter plasma on the rear surface, as observed in experiments. The reflected electrons are confined to a cone by a self-generated magnetic field, enhancing energy deposition at the rear of the target.